2019
DOI: 10.1001/jamanetworkopen.2019.11197
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Eye Gaze and Movement Differences in Visuomotor Adaptations to Varying Task Demands Among Upper-Extremity Prosthesis Users

Abstract: Key PointsQuestionIs task selection a factor in visuomotor adaptation strategies and therefore a complication in measuring outcomes for users of upper-extremity prostheses?FindingsIn this cross-sectional study of 8 prosthesis users and 16 participants with normal arm function, between tasks, prosthesis users changed their visuomotor compensatory strategies, and these strategies were different from those used by participants with normal arm function when performing the tasks. However, for a given task, prosthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 33 publications
1
55
0
Order By: Relevance
“…Although Figure 4B suggests that this window will at least be as long for amputated users, one may argue that this result is not representative for movements performed with a prosthesis. However, previous studies showed without exception that prosthetic users still fixate the target object for the majority of the reaching phase (Bouwsema et al, 2012; Sobuh et al, 2014; Chadwell et al, 2016; Hebert et al, 2019; Parr et al, 2019), albeit alternating it more often with fixations on the hand (i.e., the “switching” strategy). Moreover, this reaching phase may actually take more than twice as long as compared to the same movement performed with the anatomical limb (Sobuh et al, 2014; Hebert et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Although Figure 4B suggests that this window will at least be as long for amputated users, one may argue that this result is not representative for movements performed with a prosthesis. However, previous studies showed without exception that prosthetic users still fixate the target object for the majority of the reaching phase (Bouwsema et al, 2012; Sobuh et al, 2014; Chadwell et al, 2016; Hebert et al, 2019; Parr et al, 2019), albeit alternating it more often with fixations on the hand (i.e., the “switching” strategy). Moreover, this reaching phase may actually take more than twice as long as compared to the same movement performed with the anatomical limb (Sobuh et al, 2014; Hebert et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…In a small case study, Sobuh et al (2014) observed that the amputated participants did not use gaze to proactively plan subsequent actions in a task. Instead, they tend to switch their gaze more often between the object and the prosthetic hand to visually monitor its proper functioning (Bouwsema et al, 2012; Hebert et al, 2019). This increased visual attention is most likely to compensate for the lack of tactile and proprioceptive feedback from their prostheses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional differences in shoulder ROM were observed between use of the suction socket and the MAPS. Prosthesis users have been shown to generally have less shoulder movement compared with normative users when performing functional tasks [35] . Compared to the MAPS, maximum active shoulder ROM with the suction socket was greater for flexion/extension, similar for abduction, and less for internal/external rotation; however, during the functional task performance of the Cup Transfer Task, use of the MAPS involved a greater range of flexion/extension, and internal/ external rotation patterns more similar to normal movement.…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been several advancements to improve dexterity and restore hand grasp patterns (Gallagher, 1986;Murray, 2004;Giummarra et al, 2008), myoelectric prostheses do not provide continuous feedback to allow real-time regulation of muscle contraction. The lack of feedback poses a significant challenge to the prosthesis user; without such sensory feedback, the prosthesis needs nearconstant visual attention and mental concentration to operate (Sobuh et al, 2014;Hebert et al, 2019).…”
Section: Introductionmentioning
confidence: 99%